From Habituation to Moral Internalization: Honesty Education, Psychosocial Safety, and Student Welfare in an Islamic Boarding School - Namira; Najmul Hayat (WISE Pendidikan Indonesia, 2026)
This study investigates the internalization of honesty values through habituation practices at Sa’adatuddaren Islamic Boarding School and identifies the structural and relational conditions that support or hinder this process. Honesty is a central concern in character education, particularly in Islamic boarding schools where moral values are cultivated through religious discipline, communal living, and daily routines. Using an interpretive qualitative case study design, data were collected over three months through participant observation, semi-structured interviews with students, teachers, an administrator, and the pesantren leader, as well as document analysis. The findings show that honesty is promoted through institutionalized routines, including truthful attendance reporting, independent academic work, transparent financial responsibility, communal duties, and religious participation. However, habituation alone does not ensure deep moral internalization. Students’ honesty develops from external compliance to behavioral habituation, reflective awareness, and relational internalization when routines are supported by teacher modeling, reflective discipline, peer accountability, and psychosocial safety. This study contributes by conceptualizing honesty internalization in pesantren as an interaction between structural habituation and relational moral support within a welfare-oriented moral ecology.